Hyping the Hypothetical: Talk and Temporality in US Supreme Court Oral Arguments - Gibson, David R. (Qualitative sociology, 2024)
The US Supreme Court conducts much of its business through talk, including during oral arguments, where a central activity is the consideration of hypotheticals posed by justices. Using conversation analysis, I examine a key segment of the oral arguments for Citizens United v. FEC , one that arguably changed the course of campaign finance history. I identify the conversational devices employed to advance and contest one particular hypothetical, involving an imagined ban on books, subject to a speech-exchange system that differentially empowers justices to dictate both the terms of the discussion and the time afforded the advocate to respond to any particular question. The article offers the first disciplined qualitative analysis of interaction during oral arguments, illustrates the place of temporality in legal reasoning and argumentation, and makes several contributions to conversation analysis: it advances the study of institutional talk to a new legal setting, identifies some ways in which the machinery of talk can be harnessed for rhetorical effect, and demonstrates the analytical utility of prior knowledge of what a participant arrives to an encounter equipped to say.